A Designed Lithiophilic Carbon Channel on Separator to Regulate Lithium Deposition Behavior. Issue 2 (6th November 2021) - Xu, Sainan; Zhao, Teng; Ye, Yusheng; Yang, Tianyu; Luo, Rui; Li, Li; Wu, Feng; Chen, Renjie
Abstract: Issues with unstable SEI formation and uncontrollable lithium dendrite growth impede the practical use of lithium anode in high‐energy batteries. Herein, a lithiophilic carbon channel on separator is designed to regulate lithium deposition behavior. The designed channel is formed by carbon nanosheet with cubic cavity (CNCC) prepared by hard template method. The CNCC with a large specific surface area and good electrolyte wettability can effectively reduce the local current density. Besides, the CNCC coated separator with high Young's modulus can mechanically inhibit the growth of lithium dendrites. Notably, CNCC coating can become lithiophilic during lithium plating/striping process, which is beneficial for homogeneous lithium deposition and low lithium nucleation overpotential. As a result, based on the CNCC coated separator, the symmetric Li|Li cell cycle over 2600h at 6 mA cm −2 for 2 mAh cm −2, while the Li|Cu cell reaches average Coulombic efficiency of 98.5% at 2 mA cm −2 for 2 mAh cm −2 . Abstract : A lithiophilic carbon channel on separator is designed to regulate lithium deposition behavior. As a result, dendrite‐free deposition can be achieved and lithium nucleation overpotential can be greatly reduced. High performance of extra‐long cycle life over 2600 h in Li|Li cell and average Coulombic efficiency (CE) of 98.5% in Li|Cu cell with modified separator is realized.